Emotional intelligence and risky driving behaviour in adults. (August 2017) - Hayley, Amie C.; Ridder, Byron de; Stough, Con; Ford, Talitha C.; Downey, Luke A.
Highlights: Risky driving behaviour (RDB) predicts involvement in road-traffic accidents. Levels of emotional intelligence (EI) influence risk-taking behaviours. The link between EI, RDB and age in a group of adult drivers was assessed. Lower emotional control is associated with increased rates of RDB. Improved emotional regulation may be useful in preventing RDB in adults. Abstract: Background: Risky driving is considered a key predictive factor in road traffic accidents resulting in morbidity and mortality. Intra-individual emotional and personality factors have been shown to influence risk-taking behaviours among drivers. Despite this, there is limited research investigating the individual dimensions of these constructs and their relationship to risky driving behaviour (RDB). The current study therefore aimed to assess whether the individual dimensions of Emotional Intelligence (EI) were implicated in RDB. Methods: The sample comprised 179 adults (55% male) aged between 18 and 64 years (M = 29.85, SD = 11.46) and who currently held a valid driver's licence completed an online survey. Emotional Intelligence was assessed via self-report using the Swinburne University Emotional Intelligence Test (SUEIT), and RDB was measured using both the Brief Distracted Driving Scale (BDDS) and the Dula Dangerous Driving Index (DDDI). Results: Regression analyses revealed that 'Risky Driving' was related to greater levels of Emotional Recognition and Expression and lesser Age [ F (6, 172)  = 2.27, p  < 0.05: R 2  = 7.3%], and the Negative Emotions sub-scale of DDDI, was significantly predicted by Emotional Control and Age [ F (6, 172)  = 6.41, p  < 0.05: R 2  = 18.3%]. A mediation model incorporating Age, Emotional Control scores and the Negative Emotions driving behaviour score indicated that a significant indirect effect of Age through Emotional Control ( K 2  = 0.08, 95% CI [−0.02, −0.03]). (H [3] = 10.98, p = 0.012). Conclusions: Lower scores on specific indices of EI are associated with increased rates of RDB, suggesting that poor emotional control may impede an individuals' ability to make safe behavioural decisions when driving. The effect sizes for these models were small, however, and further research is needed to explore the contributory components in this association. Greater awareness of the role of emotional regulation and driving behaviours may be useful in preventing RDB in adults.